Adapting the NFR Framework to Aspect-Oriented Requirements Engineering - Sousa, Geórgia Maria C. de; Silva, Ismênia G. L. da; Castro, Jaelson Brelaz de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2003: Anais do XVII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2003.23860, 2003)
One of the most important principles in Software Engineering is separation of concerns. At first, the research towards applying that principle throughout the software development process has provided structured and object-oriented methods. However, when using those methods it is difficult to achieve separation of concerns such as security, performance, reliability, persistence, distribution, etc., the so-called crosscutting concerns. Hence, Aspect-Oriented Paradigm has emerged to address those issues. Similar to what happened with structured and object-oriented paradigms, in the last years, the Software Engineering community has been interested in propagating the Aspect-Oriented Paradigm to early stages of the software life cycle. The purpose of this paper is to give a contribution to Aspect-Oriented Requirements Engineering, adapting the NFR-Framework in order to improve the mapping of crosscutting non-functional requirements onto artifacts at later development stages and to make better the composition of those requirements with non-crosscutting ones.